The age of invisible machines : a practical guide to creating a hyperautomated ecosystem of intelligent digital workers - Wilson, Robb (John Wiley & Sons, Inc., 2023)
"Cut through the hype and unlock the game-changing potential of conversational AI. In Age of Invisible Machines, celebrated tech leader Robb Wilson delivers an eye-opening and startlingly insightful blueprint for leveraging conversational AI in order to make your organization self-driving--with a growing ecosystem of interconnected automations accelerating all aspects of your business. Conversational AI is changing the nature of every job at every company (starting yesterday) and this book is relevant for anyone who will be affected by the acceleration of these technologies. You'll learn how to develop a strategy for hyperautomation by identifying the outdated processes and systems holding your organization back. You'll discover ways of internalizing and orchestrating new technologies that are force-multipliers for rapid growth. A must-read for every business leader, Wilson's book debunks common myths about conversational AI while laying bare the inevitable complexity of restructuring your business to unlock the massive opportunities this new era affords"--